As mobilizações populares na criação da área de proteção ambiental Parque e Fazenda do Carmo na cidade de São Paulo - Brasil - Fulgêncio, Rodolfo Valentino (2022)
This research aimed to investigate how it developed and what were the stages of the mobilization constituted by the association of residents who demanded, together with the municipal and state public authorities, the preservation of an area, resulting in the creation of the Parque e Fazenda do Carmo Environmental Protection Area. (APA do Carmo). The methodology used in this work consisted of a case study, carried out through an analysis based on discussions fostered by the theoretical framework based on a literature review on social movements and mobilizations, which fit into this analytical process of qualitative nature. Data collection took place through interviews with leaders of the movement, at the time of the facts that occurred between the years 1985 to 1993, with the collection of information such as documents from organized civil society and documents from the public administration that were processed in the period. The relevance of the research lies in the originality of social mobilization in the creation of this area of environmental protection, adding value to current environmental issues that are themes of contemporary social mobilizations in favor of society. The results were obtained through discussions of the interviews with data analyzed in the light of the theoretical framework, evaluating its assertiveness, from the path taken in home and ecclesial meetings, in the corridors of public bodies, to its effective success with the creation of the APA do Carmo. The discussion seeks to understand the dynamism of social mobilization as an instrument for the defense of collective interests in the face of public management.